PROSPECTS AND POTENTIAL FOR THE ESTABLISHMENT OF AGROMART AT THE JEMBER STATE POLYTECHNIC PSDKU SIDOARJO - Wulandari, Sekar Ayu; Slamet, Ahmad Haris Hasanuddin; Brillyantina, Septine; Mutmainah, Dini Nafisatul; Dhandy, Rahmat (LPPM Universitas Bina Bangsa, 2025)
Agromart is an effort to utilize local potential in Sidoarjo Regency as a form of Teaching Factory (TEFA) at the Jember State Polytechnic PSDKU Sidoarjo. Agromart is also a means of learning for students through activities in business processes, ranging from product planning, operational management, and marketing to financial management. This research aims to plan the development of the Agromart business at the Jember State Polytechnic PSDKU Sidoarjo. This study employs a quantitative descriptive approach, utilizing primary and secondary data sources. The analysis methods used in this study include the Business Model Canvas (BMC) and SWOT (Strengths, Weaknesses, Opportunities, and Threats) analyses. The study results show that Agromart business has product type and quality advantages. The products offered are quality items that emphasize the local wisdom of Sidoarjo Regency. The SWOT analysis results show that Agromart business is in quadrant one. This quadrant indicates that the business is in a position of strong internal strength and has excellent external opportunities. So, a suitable strategy is to use strength to take advantage of opportunities.